Upaya Pembentukan Karakter Siswa di Madrasah Aliyah Swasta Al Fuad - Alamsyah (Journal of Legal and Cultural Analytics, 2022)
This study aims to describe the efforts to build the character of students in Al Fuad Private Madrasah Aliyah. The purpose of this study is to educate readers that madrasas have a strategic role in shaping students' morals. This type of research is a qualitative research that seeks to describe social phenomena that are developing in the present mass. The data collection techniques he did were observation and unstructured interviews and then the data were analyzed objectively and then described scientifically by following the procedures for writing scientific papers. First, madrasas play an important role by optimizing madrasas as centers of character formation. Second, madrasas strengthen the integration of fellow teachers and parents of students in order to identify the daily activities of students outside the madrasa. Third, madrasa teachers must be able to become role models for students by prioritizing ethics in words and actions according to the teachings of Islam. Fourth, the madrasa will give a reprimand if there are students who violate the norms of decency and etiquette.